IDNLearn.com provides a seamless experience for finding accurate answers. Get accurate and comprehensive answers from our network of experienced professionals.
Sagot :
To determine whether [tex]\( \frac{5\pi}{2} \)[/tex] is a solution for the equation [tex]\( 2 \sin^2 x - \sin x - 1 = 0 \)[/tex], let's go through the relevant calculations step-by-step:
1. Substitute [tex]\( x = \frac{5\pi}{2} \)[/tex] into the equation:
We need to evaluate [tex]\( \sin \left( \frac{5\pi}{2} \right) \)[/tex].
2. Find [tex]\( \sin \left( \frac{5\pi}{2} \right) \)[/tex]:
Recall that the sine function is periodic with period [tex]\( 2\pi \)[/tex]. Specifically, [tex]\( \sin( \theta + 2\pi k) = \sin( \theta ) \)[/tex] for any integer [tex]\( k \)[/tex]. Therefore:
[tex]\[ \sin \left( \frac{5\pi}{2} \right) = \sin \left( \frac{5\pi}{2} - 2\pi \right) = \sin \left( \frac{5\pi}{2} - \frac{4\pi}{2} \right) = \sin \left( \frac{\pi}{2} \right) \][/tex]
Since [tex]\( \sin \left( \frac{\pi}{2} \right) = 1 \)[/tex]:
[tex]\[ \sin \left( \frac{5\pi}{2} \right) = 1 \][/tex]
3. Substitute [tex]\( \sin \left( \frac{5\pi}{2} \right) = 1 \)[/tex] into the equation [tex]\( 2 \sin^2 x - \sin x - 1 = 0 \)[/tex]:
[tex]\[ 2 \sin^2 \left( \frac{5\pi}{2} \right) - \sin \left( \frac{5\pi}{2} \right) - 1 = 2(1)^2 - 1 - 1 = 2 - 1 - 1 = 0 \][/tex]
4. Check the result:
The left-hand side of the equation simplifies to 0, which matches the right-hand side.
Therefore, since substituting [tex]\( x = \frac{5\pi}{2} \)[/tex] into the equation [tex]\( 2 \sin^2 x - \sin x - 1 = 0 \)[/tex] yields a true statement, the value [tex]\( \frac{5\pi}{2} \)[/tex] is indeed a solution for the equation.
Thus, the correct answer is:
A. True
1. Substitute [tex]\( x = \frac{5\pi}{2} \)[/tex] into the equation:
We need to evaluate [tex]\( \sin \left( \frac{5\pi}{2} \right) \)[/tex].
2. Find [tex]\( \sin \left( \frac{5\pi}{2} \right) \)[/tex]:
Recall that the sine function is periodic with period [tex]\( 2\pi \)[/tex]. Specifically, [tex]\( \sin( \theta + 2\pi k) = \sin( \theta ) \)[/tex] for any integer [tex]\( k \)[/tex]. Therefore:
[tex]\[ \sin \left( \frac{5\pi}{2} \right) = \sin \left( \frac{5\pi}{2} - 2\pi \right) = \sin \left( \frac{5\pi}{2} - \frac{4\pi}{2} \right) = \sin \left( \frac{\pi}{2} \right) \][/tex]
Since [tex]\( \sin \left( \frac{\pi}{2} \right) = 1 \)[/tex]:
[tex]\[ \sin \left( \frac{5\pi}{2} \right) = 1 \][/tex]
3. Substitute [tex]\( \sin \left( \frac{5\pi}{2} \right) = 1 \)[/tex] into the equation [tex]\( 2 \sin^2 x - \sin x - 1 = 0 \)[/tex]:
[tex]\[ 2 \sin^2 \left( \frac{5\pi}{2} \right) - \sin \left( \frac{5\pi}{2} \right) - 1 = 2(1)^2 - 1 - 1 = 2 - 1 - 1 = 0 \][/tex]
4. Check the result:
The left-hand side of the equation simplifies to 0, which matches the right-hand side.
Therefore, since substituting [tex]\( x = \frac{5\pi}{2} \)[/tex] into the equation [tex]\( 2 \sin^2 x - \sin x - 1 = 0 \)[/tex] yields a true statement, the value [tex]\( \frac{5\pi}{2} \)[/tex] is indeed a solution for the equation.
Thus, the correct answer is:
A. True
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! Your questions find clarity at IDNLearn.com. Thanks for stopping by, and come back for more dependable solutions.